Variability in Antibiotic Treatment of Pediatric Surgical Site Infection After Spinal Fusion at A Single Institution. Issue 6 (July 2021) - Cohen, Lara L.; Birch, Craig M.; Cook, Danielle L.; Hedequist, Daniel J.; Karlin, Lawrence I.; Emans, John B.; Hresko, Michael T.; Snyder, Brian D.; Glotzbecker, Michael P.
Abstract : Background: Recent focus on surgical site infections (SSIs) after posterior spine fusion (PSF) has lowered infection rates by standardizing perioperative antibiotic prophylaxis. However, efforts have neglected to detail antibiotic treatment of SSIs. Our aim was to document variability in antibiotic regimens prescribed for acute and latent SSIs following PSF in children with idiopathic, neuromuscular, and syndromic scoliosis. Methods: This study included patients who developed a SSI after PSF for scoliosis at a pediatric tertiary care hospital between 2004 and 2019. Patients had to be 21 years or younger at surgery. Exclusion criteria included growing rods, staged surgery, and revision or removal before SSI diagnosis. Infection was classified as acute (within 90 d) or latent. Clinical resolution of SSI was measured by return to normal lab values. Each antibiotic was categorized as empiric or tailored. Results: Eighty subjects were identified. The average age at fusion was 14.7 years and 40% of the cohort was male. Most diagnoses were neuromuscular (53%) or idiopathic (41%). Sixty-three percent of patients had an acute infection and 88% had a deep infection. The majority (54%) of subjects began on tailored antibiotic therapy versus empiric (46%). Patients with a neuromuscular diagnosis had 4.0 times the odds of receiving initial empiric treatment compared with patients with an idiopathic diagnosis, controlling for infection type and time ( P =0.01). Ninety-two percent of patients with acute SSI retained implants at the time of infection and 76% retained them as of August 2020. In the latent cohort, 27% retained implants at infection and 17% retained them as of August 2020. Conclusions: Patients with acute infections were on antibiotics longer than patients with latent infections. Those with retained implants were on antibiotics longer than those who underwent removal. By providing averages of antibiotic duration and lab normalization, we hope to standardize regimens moving forward and develop SSI-reducing pathways encompassing low-risk patients. Level of Evidence: Level III. Abstract : Supplemental Digital Content is available in the text.